A narrative inquiry into a mother–child art therapy experience: A self-exploration of the therapist and the mother. (February 2016) - Shin, Seung Kyung; Choi, Sun Nam; Park, Seo Woen
Highlights: Through art therapy, this study explores the experiences of a mother and her child and what the therapy meant to the researcher and the mother in terms of self-exploration. Data were analyzed using a narrative exploration method from the literature. The experience with therapy was documented as artworks, interviews, on-site memos, and a verbatim account of the therapy process. Abstract: The experiences of a mother and her 10-year-old son who experienced a strained relationship were explored through art therapy. The experiences of the parent, her child, and the researcher within art therapy were documented as artworks, interviews, on-site memos, and a verbatim account of the process with interpretation focusing on their social meaning. Over the course of the therapy, the mother realized that she not only physically punished her child unwittingly but also found child-rearing to be difficult, experiencing guilt and anxiety. She could better understand her inner self, her thoughts and her experiences, through art therapy. The child described the mother as scary. The child described wanting to be alone because the mother seemed unable to attempt to understand the child's world. In later sessions, the mother realized that she might benefit from accepting her child as he was rather than changing him. Finally, through self-exploration, the mother realized that that her efforts to understand her child could influence his growth. The art therapy program involved the following aspects: First, the art therapy used a form of expression for exploring feelings. Second, art therapy helped resolve suppressed inner conflicts, providing a form of self-understanding to the client. Third, the fear of exposing oneself was reduced by the process of drawing. Fourth, self-reflection occurred through art engagement. Finally, the researcher explored the participants' experiences through deep self-reflection, which enabled her to provide the participants with opportunities to understand their life experiences in a more integrated way.